2009
DOI: 10.1101/gad.1785209
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for concentrating Rho1 during cytokinesis

Abstract: The small GTP-binding protein, Rho1/RhoA plays a central role in cytokinetic actomyosin ring (CAR) assembly and cytokinesis. Concentration of Rho proteins at the division site is a general feature of cytokinesis, yet the mechanisms for recruiting Rho to the division site for cytokinesis remain poorly understood. We find that budding yeast utilizes two mechanisms to concentrate Rho1 at the division site. During anaphase, the primary mechanism for recruiting Rho1 is binding to its guanine nucleotide exchange fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
177
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(192 citation statements)
references
References 61 publications
8
177
1
6
Order By: Relevance
“…S3B). SAC7 encodes a Rho1 GAP, and deletion of this gene increases the total cellular level of GTP-Rho1 (20).…”
Section: Resultsmentioning
confidence: 99%
“…S3B). SAC7 encodes a Rho1 GAP, and deletion of this gene increases the total cellular level of GTP-Rho1 (20).…”
Section: Resultsmentioning
confidence: 99%
“…Rho1 is thought to promote actin ring assembly by activating the formin Bni1 [Tolliday et al, 2002]. The localization and activation of Rho1 at the division site is, in turn, controlled by its guanine-nucleotide-exchange factor (GEF), which is regulated by the Polo kinase Cdc5 [Yoshida et al, 2006[Yoshida et al, , 2009. This cascade of activation-coupled protein recruitment to the division site defines a mechanism for the cell cycle control of actin ring assembly.…”
Section: Amr Assemblymentioning
confidence: 99%
“…Does Tus1 activate Rho1 on the vacuolar membrane? Rho1 localizes to the plasma membrane and to other sites including bud tips, the mother-bud neck, and endomembranes (McCaffrey et al 1991;Drgonova et al 1996;Qadota et al 1996;Yoshida et al 2009), while Ycf1 localizes to the vacuolar membrane (Wemmie and Moye-Rowley 1997;Mason and Michaelis 2002). Tus1 localizes to the presumptive bud site in unbudded cells and to the mother-bud neck during cytokinesis (Yoshida et al 2006;Kono et al 2008), but has not been observed on the vacuolar membrane.…”
mentioning
confidence: 99%